Operation United Assistance: Infectious Disease Threats to Deployed Military Personnel. Issue 6 (1st June 2015) - Murray, Clinton K.; Yun, Heather C.; Markelz, Ana Elizabeth; Okulicz, Jason F.; Vento, Todd J.; Burgess, Timothy H.; Cardile, Anthony P.; Miller, R. Scott
ABSTRACT: As part of the international response to control the recent Ebola outbreak in West Africa, the Department of Defense has deployed military personnel to train Liberians to manage the disease and build treatment units and a hospital for health care volunteers. These steps have assisted in providing a robust medical system and augment Ebola diagnostic capability within the affected nations. In order to prepare for the deployment of U.S. military personnel, the infectious disease risks of the regions must be determined. This evaluation allows for the establishment of appropriate force health protection posture for personnel while deployed, as well as management plans for illnesses presenting after redeployment. Our objective was to detail the epidemiology and infectious disease risks for military personnel in West Africa, particularly for Liberia, along with lessons learned from prior deployments.